A complex Xp11.22 deletion in a patient with syndromic autism: Exploration of FAM120C as a positional candidate gene for autism. Issue 12 (24th September 2014) - De Wolf, Veerle; Crepel, An; Schuit, Frans; van Lommel, Leentje; Ceulemans, Berten; Steyaert, Jean; Seuntjens, Eve; Peeters, Hilde; Devriendt, Koen
<x xml:space="preserve">Abstract</x> We present a male patient with sporadic Aarskog syndrome, cleft palate, mild intellectual disability, and autism spectrum disorder (ASD). A submicroscopic discontiguous deletion was detected on chromosome Xp11.2 encompassing FGD1, FAM120C, and PHF8. That the deletion encompassed FGD1 (exons 2–8) explains the Aarskog features while the deletion of PHF8 most likely explains the cleft palate and mild intellectual disability. We identify FAM120C as a novel X‐linked candidate gene for autism for two reasons: first, a larger deletion encompassing FAM120C segregates with autism in a previously reported family and second, there is recent evidence that FAM120C interacts with CYFIP1, part of the FMRP (Fragile X Mental Retardation Protein) network. In the current study, resequencing of FAM120C in 87 Belgian male patients with autism spectrum disorder identified no novel mutations. Expression of Fam120c in mouse tissues showed enriched expression in pituitary, cerebellum, cortex, and pancreatic islets of Langerhans. Additionally, we found a cortical expression pattern of Fam120c similar to that of Fmr1. In conclusion, FAM120C is a novel candidate gene for autism spectrum disorder based on genetic evidence and the brain expression pattern. Thereby we highlight a role for FMRP network genes in ASD. © 2014 Wiley Periodicals, Inc.